Tumoral and stromal expression of Slug, ZEB1, and ZEB2 in brain metastasis. (December 2017) - Nagaishi, Masaya; Nakata, Satoshi; Ono, Yuko; Hirata, Koji; Tanaka, Yoshihiro; Suzuki, Kensuke; Yokoo, Hideaki; Hyodo, Akio
Highlights: Epithelial to mesenchymal transition (EMT) for brain metastasis is investigated. The expression of EMT-related factors is increased in metastatic tumor cells. Stromata of brain metastases extensively express ZEB1 and ZEB2. EMT-related factors are proposed as a facilitator of brain metastasis. Abstract: Epithelial-to-mesenchymal transition (EMT) has an active role in the malignant progression of epithelial tumor cells. The aim of the study was to identify the existence of the EMT mechanism in brain metastasis. Tumors from 29 patients with brain metastases were assessed in terms of the immunoexpression of EMT-related factors including Slug, ZEB1, ZEB2, and E-cadherin in tumor cells and the surrounding mesenchymal stromal cells. The results were compared between primary tumors and their matched metastatic brain tumors. Analysis of tumor cell expression showed that Slug, ZEB1, or ZEB2 expression was found in more than 10% of the neoplastic cells in the metastatic lesions of 17 cases (59%) and in the primary lesions of 7 cases (24%, P = 0.02). The expression level of ZEB2 was negatively correlated with that of E-cadherin ( P = 0.05). There were no differences in the tumoral expression levels of Slug, ZEB1, or ZEB2 among the primary organs. Analysis of stromal cell expression revealed a global increase in ZEB1 and ZEB2 expression levels with metastases ( P < 0.0001). Quantitative analysis confirmed that messenger RNA expression of ZEB1 and ZEB2 was elevated in metastatic lesions. The increased expression of EMT-related factors in brain metastasis was found not only in tumor cells, but also in tumor-associated stromal cells. Our results suggest that EMT-related factors play a role as a facilitator of brain metastasis.